Anti‐Counterfeit Labels: Plasmonic Nanoparticles as a Physically Unclonable Function for Responsive Anti‐Counterfeit Nanofingerprints (Adv. Funct. Mater. 9/2016). (1st March 2016) - Smith, Alison F.; Patton, Paul; Skrabalak, Sara E.
Abstract : Randomly deposited plasmonic nanoparticles create optically responsive scattering patterns, which address the critical need for anti‐counterfeit, anti‐tamper labels for individual components in pharmaceuticals and electronics. On page 1315, S.E. Skrabalak and co‐workers demonstrate that the nanofingerprints are easily fabricated but difficult to reproduce, providing new, physically un‐clonable labels with the ability to detect changes in their environment.